Idiom Bahasa Jepang yang Terbentuk dari Kata Iki: Japanese Idioms Formed from the Word Iki - Syahban Danas; Rani Arfianty (Undiksha Press, 2026)
Abstract Idiom is a phrase whose meaning cannot be understood just by looking at the meanings of the individual words in it. This article discusses the analysis of idioms formed from the word